1988
DOI: 10.1007/bf01962166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a ten-minute chromogenic substrate test for identification of pathogenicNeisseria species andBranhamella catarrhalis

Abstract: A ten-minute chromogenic substrate test was evaluated for its ability to rapidly identify pathogenic Neisseria spp. and Branhamella catarrhalis. Identifications obtained with this system were compared to those obtained using conventional procedures. The test correctly identified 98.9% of 90 Neisseria gonorrhoeae, 98.3% of 60 Neisseria meningitidis, 96.2% of 26 Neisseria lactamica, and 100% of 36 Branhamella catarrhalis strains. Eight Neisseria subflava strains that grew on modified Thayer-Martin agar were prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1990
1990
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…A heavy suspension of the culture to be tested (at least a no. Some authors, however, have reported positive results with strains of Neisseria subflava, Neisseria mucosa and Neisseria sicca (17,18,21), as occurred with two strains in this study. A tablet of either PAP or GAP was added to each tube, and the tube incubated at 35 °C for 4 h. The end-points were read after adding two drops (16)(17)(18)(19).…”
Section: Superoxol and Aminopeptidasecontrasting
confidence: 71%
“…A heavy suspension of the culture to be tested (at least a no. Some authors, however, have reported positive results with strains of Neisseria subflava, Neisseria mucosa and Neisseria sicca (17,18,21), as occurred with two strains in this study. A tablet of either PAP or GAP was added to each tube, and the tube incubated at 35 °C for 4 h. The end-points were read after adding two drops (16)(17)(18)(19).…”
Section: Superoxol and Aminopeptidasecontrasting
confidence: 71%
“…8 The superoxol test requires experience to differentiate positive and negative results but gave results consistent with Neisstrip and with Phadebact Monoclonal GC in 98% of organisms tested in the prospective study. It is rapid, and cheap, but shows some positive results with other Neisseriaceae, particularly N lactamica, N meningitidis, and B catarrhalis.5 Nongonococcal isolates from gonococcal selective medium, when tested by the superoxol test and Neisstrip, gave a false positive rate which we estimate to be less than 0 1%.…”
Section: Discussionmentioning
confidence: 77%
“…mentngitidis that gave a weak reaction for GAP and one strain of N. meningitidis that gave no reaction for GAP; all three strains, however, gave positive reactions for PAP. Janda and Sobieski (1988) reported that the Identicult-Neisseria test correctly identified 98.9% of 90 N. gonorrhoeae strains, 98.3% of 60 N. meningitidis strains, 96.2% of 26 N . lactamica strains and 100% of 36 M o r .…”
Section: Discussionmentioning
confidence: 99%
“…grown on selective medium. If non-selective medium is used, non-pathogenic neisseria such as N. subJava may grow leading to misidentifications (Dillon et al 1988;Janda and Sobieski 1988). Depending on the sample site and sexual orientation of the patient isolation of non-gonococcal neisseria may vary from 0.4 to 11.4% (Young and Reid 1987).…”
Section: Discussionmentioning
confidence: 99%